Bi-specific macrophage nano-engager for cancer immunotherapy. (December 2021) - Zhao, Yu; Han, Bo; Hao, Jialei; Zheng, Yadan; Chai, Jingshan; Zhang, Zhanzhan; Liu, Yang; Shi, Linqi
Highlights: A bi-specific macrophage nano-engager (BiME) which can enhance the recognition and phagocytosis of tumor cells by macrophages. The BiME converts tumor cells into an in situ vaccine, thereby activating robust T cell-dependent antitumor responses. Engineerable surface with the flexibility to conjugate with various targeting motifs, which could recognize multiple types of tumor cells. Graphical Abstract: Table of Contents Graphic : We report a bi-specific macrophage engager (BiME) that can enhance the recognition and phagocytosis of tumor cells by macrophages to achieve effective TAA uptake and presentation, thereby activating T cell-dependent antitumor responses. Moreover, BiME can be designed with different surface properties, which allows macrophages to phagocytize the tumor cells that overexpress MET, sialic acid (SA) or CD44 receptors. ga1 Abstract: Immunotherapy holds great promise to improve the cancer treatment. The uptake of tumor-associated antigens (TAAs) by tumor-infiltrating antigen-presenting cells (e.g., macrophages) is the essential step for achieving efficient antitumor immunity. However, tumor cells usually evade phagocytosis of macrophage, resulting in inefficient TAA uptake. Herein, we demonstrate a bi-specific macrophage nano-engager (BiME) that can enhance the recognition and phagocytosis of tumor cells by macrophages, thereby achieving effective TAA uptake and presentation. BiME is composed of an albumin-based nanoparticle with a surface of crosslinked polymer network containing tumor-targeting moieties, macrophage-targeting moieties, and detachable PEG. Upon entering tumor tissues, BiME detaches the PEG and triggers phagocytosis of tumor cells by macrophages. As a result, BiME converts the tumor cells into an in situ vaccine, thereby activating robust T cell-dependent antitumor responses. By changing the tumor-targeting moieties, BiME may become a universal strategy to enhance the antitumor immunity against a broad range of solid tumors.